Chemistry of Natural Products : Phytochemistry and Pharmacognosy of Medicinal Plants (De Gruyter STEM, 2022)
Plants produce secondary metabolites that humans harness for their own benefit. About half of drugs currently in clinical use are based on these chemicals found in nature. Chemistry of Natural Products covers secondary metabolites present in medicinal plants and their biosynthesis, biological activities, and isolation and separation techniques. This book is ideal for researchers in the areas of biochemistry, medicine, and pharmacology.